The Editor-in-Chief's recommendation of this issue's article to readers; - Burak Buldur (Cumhuriyet University, 2019)
The Effect of Heat Application on Fluoride Release from Antibacterial Agent Added Glass Ionomer Cement I am pleased to inform you that I have chosen this article by Kurt et al.1 as Editor's Choice for the second issue of 2019. Glass ionomer cements (GICs) are widely used in dental procedures and pediatric dentistry. One of the most important advantages of GIC is the property of fluoride release which leads to increase ambient pH and prevent acidity by inhibiting the carbohydrate metabolism of the surrounding bacteria, resulting in the prevention of dental caries in future. This article shows that the effect of heat application leads an increased F− releasing pattern on fluoride release from antibacterial agent added The increased F− releasing pattern after the heating is believed to be promising for antibacterial GIC combinations. Happy readings in the second issue of 2019!